Supporting Literacy and Positive Identity Negotiations with Multimodal Comic Composing - Moses, Lindsey; Reid, Stephanie F. (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
This study explores how an alternative writing unit with a focus on comics, choice, and publishing supported positive identity development in a fourth-grade classroom. Many traditional literacy practices with an emphasis on skills marginalize students from under-represented populations. This study reports literacy practices that countered the production of previously established unequal relationships and instead supported bilingual students’ negotiation of positive identities. We conducted an analysis of two bilingual case studies to examine the ways in which the shift from traditional literacy skills/practices to multimodal formats provided opportunities for students who were traditionally marginalized to renegotiate identities as experts and authors.